Intestinal hydrolysis and microbial biotransformation of diacetoxyscirpenol-α-glucoside, HT-2-β-glucoside and N-(1-deoxy-d-fructos-1-yl) fumonisin B1 by human gut microbiota in vitro. (3rd July 2020) - Daud, Noshin; Currie, Valerie; Duncan, Gary; Busman, Mark; Gratz, Silvia W.
Abstract: Fusarium mycotoxins are common contaminants in cereals and often co-occur with plant-derived mycotoxin sugar conjugates. Several of these modified mycotoxins are not degraded in the small intestine and hence carried through to the large intestine where microbial transformation may occur. This study aims to assess the gastrointestinal stability of the trichothecenes HT-2 toxin (HT-2), HT-2-β-glucoside (HT-2-Glc), diacetoxyscirpenol (DAS), DAS-α-glucoside (DAS-Glc) and fumonisin B1 (FB1 ), N -(1-deoxy-d -fructos-1-yl) fumonisin-B1 (NDF-FB1 ). All tested modified mycotoxins were stable under upper gastrointestinal (GI) conditions. In faecal batch culture experiments, HT-2-Glc was hydrolysed efficiently and no further microbial biotransformation of HT-2 was observed. DAS-Glc hydrolysis was slow and DAS was de-acetylated to 15-monoacetoxyscripenol. NDF-FB1 was hydrolysed at the slowest rate and FB1 accumulation varied between donor samples. Our results demonstrate that all tested modified mycotoxins are stable in the upper GI tract and efficiently hydrolysed by human gut microbiota, thus potentially contributing to colonic toxicity. Hence the microbial biotransformation of any novel modified mycotoxins needs to be carefully evaluated.